Three-dimensional image reconstruction of macroscopic objects from a single digital hologram using stereo disparity - Ozgurun, Baturay; Tayyar, Duygu Önal; Agiş, Kaan Özer; Özcan, Merıç (OSA - The Optical Society info@osa.org, 2017)
We present depth extraction of macroscopic three-dimensional (3D) objects from a single digital hologram using stereo disparity. The method does not require the phase information of the hologram but two perspectives of the scene, which are easily obtained by dividing the hologram into two parts (two apertures) before the reconstruction. Variation of the hologram division is countless since each piece of a single hologram contains all the information regarding the scene; therefore, stereo disparity can be calculated along any arbitrary direction. We investigated the effects of gradual and sharp divisions of the holograms for the disparity map calculations, specifically for divisions in the vertical, horizontal, and diagonal directions. After obtaining the depth map from the stereo images, a regular two-dimensional image of the object is merged with the depth information to form 3D visualization of the object. Holograms were recorded with a rigid endoscope, and experimentally obtained depth profiles of the objects are in very good agreement with the actual profiles. © 2018 Elsevier B.V., All rights reserved.
Keywords: Computerized tomography; Image reconstruction; Lithography; Stereo image processing; Three dimensional computer graphics; Arbitrary direction; Depth information; Digital holograms; Macroscopic objects; Phase information; Three-dimensional (3D) objects; Three-dimensional image reconstruction; Two dimensional images; Holograms